ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT PERBANKAN PADA BANK UMUM DI BURSA EFEK INDONESIA - Rensa Andalusia, - (2019)
This research is a quantitative research that aims to determine the influence of Liquidity, Non Performing Loans, Capital Adequacy and Third Party Funds to Bank Credit Distribution (Study on Commercial Bank in Indonesia period of 2015-2017). The population used in this study is a Commercial Bank listed on BEI period of 2015-2017. By using purposive sampling method, obtained as many 29 banks as research samples. The type of data used is secondary data. Hypothesis testing in this research use panel data regression analysis with the program Eviews 9.0 and significant level 0,05. The results of this study indicate that Liquidity measured with Loan to Deposit Ratio (LDR) and Third Party Funds have a positive and significant effect on Banking Credit Disribution, while Capital Adequacy as measured by Capital Adequacy Ratio (CAR) and Non Performing Loan (NPL) does not effect on Banking Credit Distribution.